1992
DOI: 10.1017/s0033822200064158
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating of Fourteen Dead Sea Scrolls

Abstract: ABSTRACT. The name Dead Sea Scrolls refers to some 1200 manuscripts found in caves in the hills on the western shore of the Dead Sea during the last 45 years. They range in size from small fragments to complete books from the holy scriptures (the Old Testament). The manuscripts also include uncanonized sectarian books, letters and commercial documents, written on papyrus and parchment. In only a few cases, direct information on the date of writing was found in the scrolls. In all other cases, the dating is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 14 publications
5
51
0
Order By: Relevance
“…However, it was only with the introduction of AMS that dating material from the scrolls and not samples associated with them was finally possible. [75,76] Even though a few discrepancies were found, the results of radiocarbon dating essentially confirmed palaeographic considerations. However, also in this case, 14 C results have led to polemics and discussion.…”
Section: Examples Of Applicationssupporting
confidence: 58%
“…However, it was only with the introduction of AMS that dating material from the scrolls and not samples associated with them was finally possible. [75,76] Even though a few discrepancies were found, the results of radiocarbon dating essentially confirmed palaeographic considerations. However, also in this case, 14 C results have led to polemics and discussion.…”
Section: Examples Of Applicationssupporting
confidence: 58%
“…For comparison, 2 samples (KLR-2525 and KLR-2527) were cleaned using only the AAA procedure in a manner similar to that of Bonani et al (1992) and Jull et al (1995). The AAA method by itself is insufficient to remove castor oil, as reported by Rasmussen et al (2001).…”
Section: Cleaning Experiments With 2 × 15 Minutes In Hexane In Ultrasoundmentioning
confidence: 99%
“…If modern castor oil is present and is not removed prior to dating, the 14 C dates will be skewed artificially towards modern values. In Rasmussen et al (2001), it was shown that the standard AAA pretreatment procedure used in the 2 previous studies dating Dead Sea Scroll samples (Bonani et al 1992;Jull et al 1995) is not capable of removing castor oil from parchment samples. In the present work, we show that it is unlikely that castor oil reacts with the amino acids of the parchment proteins, a finding which leaves open the possibility of devising a cleaning method that can effectively remove castor oil.…”
mentioning
confidence: 99%
“…A feature of the Zurich study was an apparent displacement of basic cal BCE/CE values toward older ages than expected from known dates and those estimated from paleographical studies, as noted by Bonani et al (1992) and analyzed by Rodley (1993). However, as pointed out to us by Doudna (personal communication 1998;unreferenced) Obviously, the papyrus was not cut after the date of recording, so some other common factor appears to have affected these measurements.…”
Section: C Dating Of Scroll Samples Extension Of Results Using Stumentioning
confidence: 84%